Collisions between droplets of liquids of different viscosity and composite fuel particles; Experimental Thermal and Fluid Science; Vol. 173 - Islamova A. G. Anastasiya Gomilievna; Tkachenko P. P. Pavel Petrovich; Shlegel N. E. Nikita Evgenjevich; Shulyaev S. A. Stanislav Antonovich; Strizhak P. A. Pavel Alexandrovich (2026, 2026)
Title screen